Anger rumination and aggressive behaviour in borderline personality disorder. (3rd September 2015) - Martino, Francesca; Caselli, Gabriele; Berardi, Domenico; Fiore, Francesca; Marino, Erika; Menchetti, Marco; Prunetti, Elena; Ruggiero, Giovanni Maria; Sasdelli, Anna; Selby, Edward; Sassaroli, Sandra
Abstract Background Emotional instability and dyscontrolled behaviours are central features in borderline personality disorder (BPD). Recently, some cognitive dysfunctional mechanisms, such as anger rumination, have been found to increase negative emotions and promote dyscontrolled behaviours. Even though rumination has consistently been linked to BPD traits in non‐clinical samples, its relationship with problematic behaviour has yet to be established in a clinical population. Aim The purpose of the study was to explore the relationships between emotional dysregulation, anger rumination and aggression proneness in a clinical sample of patients with BPD. Methods Enrolled patients with personality disorders (93 with BPD) completed a comprehensive assessment for personality disorder symptoms, anger rumination, emotional dysregulation and aggression proneness. Results Anger rumination was found to significantly predict aggression proneness, over and above emotional dysregulation. Furthermore, both BPD diagnosis and anger rumination were significant predictors of aggression proneness. Conclusion Future research should examine whether clinical techniques aimed at reducing rumination are helpful for reducing aggressive and other dyscontrolled behaviours in treating patients with BPD. Copyright © 2015 John Wiley & Sons, Ltd.